Lived experiences of racial and ethnic minorities in the lodging industry: a phenomenological study - Birinci, Hasan (Kansas State University, 2023)
Racial and ethnic minorities make up more than half of the lodging workforce in the United States yet hold a disproportionally low percentage of management and executive-level positions. The purpose of this study was to explore the lived experience of hotel managers of racial and ethnic minorities who have reached a management level. The problem examined by this study is what factors affect the low representation of racial and ethnic minority managers and how a small percentage of racial and ethnic minority managers may have overcome these barriers to achieve an advanced leadership position. The phenomenological qualitative study was completed using semi-structured interviews with 11 racial and ethnic minority managers in the lodging industry. NVivo12 software was used to help organize data and identify patterns and themes associated with the lived experiences of the perceived career barriers of the racial and ethnic minority managers in the lodging field. The research questions explored career barriers and challenges, preparation for career advancement, perceptions of the organization's diversity climate, and essential skills and attributes for success related to their career journeys to leadership in the lodging industry. The qualitative data analysis revealed five major themes: (a) career advancement barriers, (b) perceived diversity climate, (c) personal and professional preparation, (d) networking and mentoring, and (e) essential skills and attributes for success. The results revealed that the lack of representation of racial and ethnic minorities in management in the lodging industry is related to perceived career advancement barriers such as discriminatory treatment, implicit bias, access barriers, language issues, ageism, difficulty becoming accepted and channeling to lower-level position. The findings revealed variables to overcome potential career barriers, including joining helpful networking opportunities, finding good mentors, and preparing for personal and professional growth. Furthermore, variables important for career success included working hard and having a good work ethic, having effective communication skills, being adaptable, exceeding requirements, having a strong demeanor, being open to learning, and being available for opportunities.
Keywords: Diversity; Diversity management; Organizational inclusion; Perception of diversity climate; Phenomenology